FİBROMİYALJİ SENDROMLU HASTALARDA PLAZMA NESFATİN-1 DÜZEYİNİN KLİNİK VE YAŞAM KALİTESİ ÜZERİNE ETKİSİ - ELBASTI, MUHAMMET ŞAHİN (Fırat Üniveristesi, 2021)
Bu çalışmanın amacı; fibromiyalji sendromunda (FMS) ağrı şiddeti, hastalık aktivitesi, anksiyete, depresyon, uyku kalitesi ve yaşam kalitesi gibi klinik parametreler ile serum nesfatin-1 düzeyi arasındaki ilişkiyi araştırmaktır. Çalışmaya 18-65 yaş arası, 82 FMS tanılı hasta ve 82 kontrol hastası alındı. Hastaların ağrısı vizüel analog skalası (VAS), fonksiyonel durumu fibromiyalji etki anketi (FEA), duygu durumları Beck depresyon (BECK-D) ve Beck anksiyete (BECK-A) ölçeği, uyku bozukluğu Pittsburgh Uyku Kalitesi İndeksi (PUKI) , yaşam kalitesi Short Form-36 (SF-36) ile değerlendirildi. Hastaların rutin kontrolleri için bakılan tam kan sayımı, kan sedimentasyon değerleri, serum C-reaktif protein (CRP), romatoid faktör (RF), karaciğer fonksiyon testlerinden; alanin transaminaz (ALT) ve aspartat transaminaz (AST), kreatin kinaz (CK), kreatinin, parathormon (PTH), D vitamini ve tiroid stimulan hormon (TSH) tetkikleri yapıldı. Nesfatin-1 düzeyleri, ELISA yöntemi kullanılarak tespit edildi, ölçülen değerler ng/L cinsinden kaydedildi. Fibromiyalji sendromlu hastalar ile kontrol hastaları arasında demografik özellikler açısından anlamlı bir fark yoktu. Klinik parametreler karşılaştırıldığında, FMS hastalarında FEA, VAS, BECK-A, BECK-D ve PUKI skorları kontrollere göre anlamlı olarak yüksekti (p <0.05). Fibromiyalji sendromlu hastaların yaşam kalitesi skorları kontrol grubuna göre anlamlı derecede düşüktü (p<0,05). Serum nesfatin-1 konsantrasyonu FMS'li hastalarda anlamlı olarak düşüktü (p <0.05). Fibromiyalji sendromlu hasta grubunda nesfatin-1 ile BECK-A skoru, BECK-D skoru arasında anlamlı pozitif korelasyon (p<0,05) saptanırken, nesfatin-1 ile vücut kitle indeksi (VKI) arasında anlamlı negatif korelasyon (p<0,05) saptandı. Düşük plazma nesfatin-1 seviyeleri FMS'deki patolojik değişikliklere katkıda bulunabilir. Ek olarak nesfatin-1, FMS'de anksiyete ve depresyon ile ilişkili yanıtların arabuluculuğunda da yer alabilir. Anahtar Kelimeler: FMS, nesfatin-1, anksiyete, depresyon, yaşam kalitesi

The aim of this study is; to investigate the relationship between serum nesfatin-1 level and clinical parameters such as pain intensity, disease activity, anxiety, depression, sleep quality and quality of life in fibromyalgia syndrome (FMS). Eighty two patients with FMS and 82 control patients, aged 18-65 years, were included in the study. Patients; pain visual analogue scale (VAS), functional status fibromyalgia impact questionnaire (FEA), moods Beck depression (BECK-D) and Beck anxiety (BECK-A) scale, sleep disorder Pittsburgh Sleep Quality Index (PUKI), quality of life Short Form -36 (SF-36). From the complete blood count, blood sedimentation values, serum C-reactive protein (CRP), rheumatoid factor (RF), liver function tests for the routine control of the patients; alanine transaminase (ALT) and aspartate transaminase (AST), creatine kinase (CK), creatinine, parathyroid hormone (PTH), vitamin D and thyroid stimulating hormone (TSH) tests were performed. Nesfatin-1 levels were determined using enzyme linked immunosorbent assay (ELISA) method, measured values were recorded in ng/L. There was no significant difference in demographic characteristics between patients with fibromyalgia syndrome and control patients. When clinical parameters were compared, FEA, VAS, BECK-A, BECK-D and PUKI scores were significantly higher in FMS patients compared to controls (p <0.05). Quality of life scores of patients with fibromyalgia syndrome were significantly lower than the control group (p <0.05). Serum nesfatin-1 concentration was significantly lower in patients with FMS (p <0.05). Significant positive correlation (p <0.05) was found between nesfatin-1 and BECK-A score and BECK-D score in patients with fibromyalgia syndrome, while significant negative correlation was found between nesfatin-1 and body mass index (BMI) (p <0.05 ) was detected. Low plasma nesfatin-1 levels may contribute to pathological changes in FMS. Additionally, nesfatin-1 may be involved in the mediation of anxiety and depression-related responses in FMS. Keywords: FMS, nesfatin-1, anxiety, depression, quality of life
The effect of plasma nesfatin-1 level on clinical and quality of life in patients with fibromyalgia syndrome
Keywords: Fiziksel Tıp ve Rehabilitasyon